MODERN LABORATORY DIAGNOSTICS OF RHEUMATOID ARTHRITIS: NEW DIAGNOSTIC METHODS, NEW POSSIBILITIES - Isomadinova Lola Kamoliddinovna; Kudratova Zebo Erkinovna; Shamsiddinova Dilorom Kamariddinovna (Western European Studies, 2024)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease that affects the joints and can lead to destruction of joint tissue, disability and reduced quality of life in patients. The human immune system produces antibodies (proteins) that fight viruses and bacteria as well as foreign substances. In rheumatoid arthritis, antibodies are produced against healthy cells and tissues in the body. These are called autoantibodies. An inflammatory process within the joint occurs, in which the synovial membrane thickens and becomes more dense (pannus) and the joint itself swells. As the pannus grows, the articular cartilage becomes deformed, which leads to weakening of ligaments, tendons and muscles, and in the most advanced cases to lysis (dissolution) of bone heads. Against this background, the bones forming the joint begin to deform and deteriorate.Timely diagnosis of RA is crucial for initiating treatment and preventing disease progression. Modern methods of laboratory diagnostics play a key role in detecting RA and assessing its severity.
Keywords: rheumatoid arthritis; antibodies to cyclic citrullinated peptide; patient